2019
DOI: 10.1098/rsbl.2019.0015
|View full text |Cite
|
Sign up to set email alerts
|

Transitive inference in Polistes paper wasps

Abstract: Transitive inference (TI) is a form of logical reasoning that involves using known relationships to infer unknown relationships (A . B; B . C; then A . C). TI has been found in a wide range of vertebrates but not in insects.Here, we test whether Polistes dominula and Polistes metricus paper wasps can solve a TI problem. Wasps were trained to discriminate between five elements in series (A 0 B2, B 0 C2, C 0 D2, D 0 E2), then tested on novel, untrained pairs (B versus D). Consistent with TI, wasps chose B more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…In such cases, when selection is stronger on social competence, we additionally predict that the general cognitive system can become specialized to the social domain through the emergence of cognitive abilities especially adapted for social decision‐making. This could be the case, for example, of transitive inference, a cognitive ability that allows animals to recognize dominance hierarchies but that can be useful outside the social domain (MacLean, Merritt, & Brannon, ; Tibbetts, Agudelo, Pandit, & Riojas, ). Animals in this circumstance develop an enhanced cognitive system that although general is also predominantly social (Figure a).…”
Section: The Social Specialization Of the Cognitive Systemmentioning
confidence: 99%
“…In such cases, when selection is stronger on social competence, we additionally predict that the general cognitive system can become specialized to the social domain through the emergence of cognitive abilities especially adapted for social decision‐making. This could be the case, for example, of transitive inference, a cognitive ability that allows animals to recognize dominance hierarchies but that can be useful outside the social domain (MacLean, Merritt, & Brannon, ; Tibbetts, Agudelo, Pandit, & Riojas, ). Animals in this circumstance develop an enhanced cognitive system that although general is also predominantly social (Figure a).…”
Section: The Social Specialization Of the Cognitive Systemmentioning
confidence: 99%
“…This is, of course, not evidence bees or other insects cannot rank. As we noted above, Polistes wasps have solved a transitive inference task that controlled for reinforcement history [13] suggesting a capacity to compare and rank. Honey bees, however, failed at a similar task [63].…”
Section: Discussionmentioning
confidence: 94%
“…This is, of course, not evidence bees or other insects cannot rank. As we noted above, Polistes wasps have solved a transitive inference task that controlled for reinforcement history [12] suggesting a capacity to compare and rank. Honey bees, however, failed at a similar task [55].…”
Section: Discussionmentioning
confidence: 94%
“…Probability maximising requires a capacity to compare the value of different options and to rank them accordingly. Until recently this kind of cognition was presumed to be too complex for insects, but bees do have the capacity to learn abstract relationships between stimuli [9][10][11], and a recent study with Polistes wasps showed the wasps could pass a behavioural test considered indicative of the capacity for transitive inference [12]. This requires arranging stimuli in a ranked order [12] suggesting that Polistes dominula and Polistes metricus at least have a capacity for ranking of stimuli.…”
Section: Introductionmentioning
confidence: 99%